2019
DOI: 10.1002/cncr.32143
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of a wearable technology‐based intervention for increasing moderate to vigorous physical activity and reducing sedentary behavior in breast cancer survivors: The ACTIVATE Trial

Abstract: Background The benefits of an active lifestyle after a breast cancer diagnosis are well recognized, but the majority of survivors are insufficiently active. The ACTIVATE Trial examined the efficacy of an intervention (use of the Garmin Vivofit 2 activity monitor coupled with a behavioral feedback and goal‐setting session and 5 telephone‐delivered health coaching sessions) to increase moderate to vigorous physical activity (MVPA) and reduce sedentary behavior in breast cancer survivors. Methods This randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
193
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(201 citation statements)
references
References 48 publications
5
193
1
2
Order By: Relevance
“…Many of the strengths and limitations described in the ACTIVATE Trial primary outcomes article apply to this brief report. Because of funding constraints, we were unable to test the efficacy of wearable technology alone in a randomized trial setting: a 3‐armed trial comparing the primary intervention, the abridged intervention, and a control condition would have been ideal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the strengths and limitations described in the ACTIVATE Trial primary outcomes article apply to this brief report. Because of funding constraints, we were unable to test the efficacy of wearable technology alone in a randomized trial setting: a 3‐armed trial comparing the primary intervention, the abridged intervention, and a control condition would have been ideal.…”
Section: Discussionmentioning
confidence: 99%
“…The ACTIVATE Trial examined the efficacy of a wearable technology‐based intervention (using the Garmin Vivofit 2 activity tracker, coupled with a behavioral feedback and goal‐setting session and 5 telephone‐delivered health coaching sessions) delivered over a 12‐week period (T1‐T2) to increase moderate to vigorous physical activity (MVPA) and reduce sitting time in breast cancer survivors. The intervention successfully increased MVPA (between‐group change = 69 min/wk; 95% CI = 22‐116) and decreased sitting time (−37 min/d; 95% CI = −72 to −2) …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…We recently completed the ACTIVity And TEchnology (ACTIVATE) Trial, an intervention that examined the efficacy of a wearable technology‐based intervention (using the Garmin Vivofit 2, with a behavioral feedback and goal setting session, and five telephone‐delivered health coaching sessions). We reported that the intervention successfully increased moderate to vigorous physical activity (MVPA) (between group change = 69 minutes/week, 95% CI: 22, 116) and decreased sitting time (−37 minutes/day, 95% CI: −72, −2), and the MVPA changes were sustained 3 months after the intervention …”
Section: Introductionmentioning
confidence: 99%
“…Also, most behavioural intervention studies assessing the effects of physical activity level usually incorporate a behaviour change model. [62] This helps in developing lifestyle promotion strategies to accumulate physical activity as well as appropriate walking plans for enhancing, motivating, and overcoming barriers to physical activity. Importantly, such behavioural intervention studies are driven by speci ed behaviour change theories/models aimed at identifying modi able predictors of subjects' behaviours towards physical activity [63].…”
Section: Implications For Researchmentioning
confidence: 99%